IMPLEMENTASI KEBIJAKAN PROGRAM KELUARGA BERENCANA (KB) DI KABUPATEN KAMPAR (Studi Kasus Partisipasi KB Pria Di Kecamatan Kampar Kiri Hilir) - Rizal, Muhammad; Yulini, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Family planning program (KB) is the action that helps individuals or married couples with the aim to form a quality family, through birth, set the interval between pregnancies. The targets of the Program active participants to KB men contained in the National medium term development plan 2010-2014, that increasing participants man becomes 4.5 per cent of the number of pairs of fertile age. Problems in the implementation of the Program for men is the use of KB contraceptives long-term man participant family planning who is still limited as well as socializing or counseling about man vasectomy family planning who is still low, consequently, the lack of understanding of the father/husband in the family planning.In this research the concept of theory used in reference to the policy implementation theory propounded by Wahad that implementation as a process implementing the policy decisions that are normally in the form of laws, regulations, judicial decisions, administrative, Executive order, or presidential decree. Based on Act No. 52 of 2009 about family planning, the scope of the activities of the policy of family planning Program (KB), include family planning and implementation efforts improved access and quality of service information, education and contraceptives.The results of the research implementation of the policy of family planning Program (KB) in the District of Kampar (case study on the participation of men in district of Kampar KB Left Downstream, not to run optimally, where family coaching efforts (counseling) provided by the family planning Field extension officers (PLKB) subdistrict of Kampar Kiri Hilir against Couples Age fertile (PUS)/KB Men not supported by improved access to information and counselling (education) low-impact man KB understanding and participation of men in air-KB. Factors that affect the institutional structure that is in district, culture, managing resources (PLKB) is still scanty in quantity and quality, coordination and dissemination of the program not running man KB, implies understanding and participation of men/husbands for KB.Key words: Family Planning Program (KB), Participation, Vasectomy (Medical Operation Man/FOOL), Family Planning Field Extension Officers (PLKB).